2021
DOI: 10.1002/iid3.418
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric asthma control during the COVID‐19 pandemic

Abstract: Background The lockdown imposed by the COVID‐19 pandemic resulted in a completely different style of life with possible effects on the attitude toward their disease in patients with chronic lung disease, such as asthma. The aim of our study was to investigate in asthmatic children the level of asthma control and the maintenance therapy used during the lockdown. Methods Among asthmatic children attending our clinic, we identified those who had been prescribed the same th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 21 publications
(33 reference statements)
2
39
0
Order By: Relevance
“… 12 The children who increased their use of asthma medicines in March 2020 had poorer asthma control than in March 2019. 12 Also, during the first wave of the pandemic, it was thought that people with moderate‐to‐severe asthma might face a higher risk of severe COVID‐19 disease, 28 and this may have increased the use of asthma medicines. Thus, the increase in the first quarter in our study may have been due to worse asthma control and the fear of severe COVID‐19 disease in early 2020.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 The children who increased their use of asthma medicines in March 2020 had poorer asthma control than in March 2019. 12 Also, during the first wave of the pandemic, it was thought that people with moderate‐to‐severe asthma might face a higher risk of severe COVID‐19 disease, 28 and this may have increased the use of asthma medicines. Thus, the increase in the first quarter in our study may have been due to worse asthma control and the fear of severe COVID‐19 disease in early 2020.…”
Section: Discussionmentioning
confidence: 99%
“… 11 In addition, asthma control appeared to improve in about 20%–30% of children during spring 2020, based on an Italian study and a global survey of practitioners. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…In recent study that analysed the impact of the COVID-19 pandemic and lockdown in asthmatic children, the lockdown had an impact on children's approach to their upkeep therapy compared to the previous year, in fact, a bigger proportion of children took a daily therapy higher than prescribed. As far as asthma control is concerned, they found that the level of asthma control was meaningfully improved during the lockdown compared to the same period of the previous year, [24] because of the reduced exposure to typical asthma triggers due to confinement even though their level of physical activity was not ascertained.…”
Section: Main Textmentioning
confidence: 99%
“…In Italy, in general, children experienced reduced access to the ER during the pandemic with short‐term worsening of underlying chronic conditions, delayed diagnosis, or increased severity of clinical manifestations upon admission 11–13 . This does not appear to be the case for children with SCD.…”
Section: Figurementioning
confidence: 99%
“…In Italy, in general, children experienced reduced access to the ER during the pandemic with short-term worsening of underlying chronic conditions, delayed diagnosis, or increased severity of clinical manifestations upon admission. [11][12][13] This does not appear to be the case for children with SCD. Reduced access to ER services for the typical acute manifestations of SCD was not due to a barrier, but to a reduction of the clinical complications themselves.…”
mentioning
confidence: 95%